NEUROCIÊNCIA E AS PRÁTICAS DE LEITURA – UM NOVO OLHAR PARA O PROCESSO ENSINO- APRENDIZAGEM NOS PRIMEIROS ANOS DE ESCOLARIZAÇÃO - Guerino, Silvana Lúcia Costabeber (2018)
The present study had the objective of investigating projects of reading encourage practices in the school environment and their contributions to the teaching-learning process of elementary school students, through the neuroscience approach. The research is a qualitative and quantitative case study methodology. The sample was done with sixteen (16) students from a fifth grade of Elementary School I, five teachers and school principals, from a public school in Santa Maria city, Rio Grande do Sul State. The collection was carried out in 2017, with the application of the Portuguese Language, Mathematics and Nature Sciences tests, from the Diagnostic Evaluation of the Evalu-BH Project, to evaluate students' performance, as well as observations of reading practices in the classroom and interviews with teachers and school principals. The results showed that the reading practices in the school routine contributed significantly to the students' cognitive development, not only in Portuguese Language, but in Science and Mathematics, besides itis a source to stimulate the students brains, and also to promote knowledge that leads to a criticalreflexive posture, vehy relevant to their integral formation. In conclusion, reading projects at the school routine is a potential agents of learning, as seen by the Neuroscience approach, since they allow advances in the cognitive development of students, like observed in their autonomous posture and protagonist of learning in class. Therefore, in order to teach for promoting meaningful learning, teachers and school principals should be encouraged to invest in reading and literacy practices, along with pedagogical action in the school context